OPTIMAL PLACEMENT OF DENTAL IMPLANTS: ASSESSING BONE, SOFT TISSUE, DEPTH, AND POSITION FOR LONG-TERM SUCCESS - Javier Arturo Paz Hernández; Adina Maria Baroi; Mihaela Papusa Vasiliu; Daniela Tomita; Oana Cucoveica; Cristina Albert; Carmen Stadoleanu (Romanian Journal of Oral Rehabilitation)
The optimal placement of dental implants significantly influences their long-term functional and aesthetic success. This article consolidates evidence-based strategies, emphasizing the importance of key factors such as soft tissue thickness, keratinized tissue presence, implant depth, three-dimensional positioning, and crown material selection. Results demonstrate that a minimum soft tissue thickness of 2 mm effectively reduces marginal bone loss by up to 0.8 mm and enhances implant stability. Similarly, at least 2 mm of keratinized tissue is essential for reducing peri-implant diseases and promoting tissue health. Implant placement 3-4 mm below the gingival margin, with sufficient buccal bone support, minimizes gingival recession and supports esthetic outcomes. Zirconia crowns and polished surfaces are shown to significantly lower plaque accumulation and inflammation, enhancing peri-implant health. Furthermore, platform switching consistently reduces bone loss by 0.3–0.8 mm, particularly in mechanically stressed regions, while custom healing abutments preserve soft tissue architecture and improve integration. These findings provide a comprehensive framework for achieving predictable and sustainable outcomes in implantology, integrating advanced techniques and precise clinical parameters.